A review of antimicrobial usage practice in livestock and poultry production and its consequences on human and animal health. - Islam, Md Ariful; Bose, Palash; Rahman , Md Zaminur; Muktaruzzaman , Muhammad; Sultana, Papia; Ahamed, Tanvir; Khatun, Mst Minara (Journal of Advanced Veterinary and Animal Research, 2024)
Antimicrobials are employed in the control of contagious illnesses in humans and animals and are also utilized as growth enhancers in livestock and poultry. Improper application of antibiotics results in the development of multi-drug-resistant (MDR) bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant S. aureus (VRSA), colistin-resistant, extended-spectrum beta-lactamase (ESBL)-producing E. coli, and fluoroquinolone-resistant Salmonella. Transmission of MDR bacteria happens among animals, from human to animal, and vice versa, resulting in treatment failure, increased treatment cost, and high morality. In this article, we analyzed the recent publications of the current antimicrobial application practices in livestock and poultry farms and the development of antimicrobial resistant (AMR) bacteria in livestock and poultry and its adverse effects on human and animal health using PubMed, Google Scholar, and Google. Citations from published articles were also analyzed. Several drug-resistant bacteria, including MRSA, VRSA, colistin-resistant strains, ESBL-producing E. coli, and fluoroquinolone-resistant Salmonella, have emerged due to heavy antibiotic application in cattle and poultry, according to the analysis. Transmission happens between people and animals as well as throughout the production chain, which raises the chance of failure of antibiotic therapy and fatality. To stop the proliferation of drug-resistant bacteria, it is important to ensure the proper use of antibiotics in livestock and poultry. Especially in developing nations, strict control and implementation of antimicrobial rules are necessary. To successfully address antimicrobial resistance and lessen dependency on antibiotics, alternative disease management strategies in livestock and poultry must be developed. J. Adv. Vet. Anim. Res., 11(3): 675–685, September 2024 http://doi.org/10.5455/javar.2024.k817